THE ROLE OF UIN ALAUDDIN MAKASSAR LIBRARY IN SUPPORTING “MBKM” PROGRAM (International Conference on Social and Islamic Studies, 2021)
An academic library plays important roles in supporting teaching, research, and learning activities in the institution. All services that the academic library provides must adapt to current and future conditions of the library users, especially how the library can support the current program in Indonesian universities called as Independent Learning Independent Campus (MBKM). This paper is aimed to describe the role of UIN Alauddin Makassar’s Library in supporting Merdeka Belajar Kampus Merdeka (MBKM). This qualitative study gathered the data through literatures and based on observations.The data from literatures were analysed by analysing the literature contents while the observed data used to strengthen the findings. This article showed that certain programs or activities that might be applied within the library are; enrich the number and forms ofther collection, active interaction with the civitas, making active learning atmosphere, reference librarian or specialist subject, supporting accreditation in each study program, bibliometrics, and trained librarians.